PENGARUH SUHU INKUBASI TERHADAP AKTIVITAS LIPASE DAUN PEPAYA (Carica papaya L) YANG DIAMOBILISASI DALAM PASIR LAUT - Fisty Sumangkut; Nurhaeni; Ni Ketut Sumarni; Erwin Abdul Rahim (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2019)
The silica content in sea sand can be used to immobilize lipase from papaya leaf. Research on the influence of incubation temperature on sea sand immobilized lipase from papaya leaf (Carica papaya L) has been carried out. The aim of research is determining the influence of incubation temperature on sea sand immobilized lipase from papaya leaf (Carica papaya L). The method used in this study was a completely randomized design with temperature at 30, 40, 50, 60, 70°C. The results show that lipase from papaya leaf (Carica papaya L) had successfully immobilized in the sea sand and the optimum temperature stability of lipase immobilized in sea sand at 50°C with an activity is 53.000 µmol/g.jam Keywords : immobilized, lipase, papaya leaf, sea sand.